Rally post-terrorism - Shuai Chen (Journal of Population Economics, 2025)
This study examines whether the “rally 'round the flag” phenomenon is present after terrorist attacks, and investigates explanations for this increase in confidence in national political institutions and approval of the country leader's job performance. I exploit variations in terrorist occurrences and results (success or failure) across subnational EU regions where at least one attack took place during the data period. I show empirically that both terrorist occurrences and results are plausibly exogenous to the prior political and economic climate. Conducting a difference-in-differences analysis, I compare changes in political confidence and approval among individuals who were exposed to an attack in their region with those who were not. Utilizing another more sophisticated identification, I also compare such political changes after successful attacks with those after failed attacks. I find that post-terrorism, individual political confidence and support significantly increased by more than 10 percentage points, and that this political increment was over 5 percentage points after successful attacks relative to failed ones. Such rally effects were temporary and faded away within a year. Furthermore, I explore various potential channels suggesting patriotism and civic engagement as mechanisms while rejecting perceived economic capture and political acquisition as alternative explanations.
Keywords: D74; H12; P16; 330; Rally 'round the flag effect; Terrorism; Confidence in institutions; Political approval; Patriotism; Civic engagement; Economic capture; Political acquisition